LANDSCAPE DOCTRINE AND ITS IMPORTANCE IN THE SCIENTIFIC AND PRACTICAL STUDY OF NATURAL RESOURCES OF REGIONS - Komiljonovna, Ergasheva Mavjuda; Khamitovich, Rakhimov Olim (The journal of contemporary issues in business and government, 2021)
The article deals with the creation and development of landscape education, issues related to the scientific and practical study of natural resources of the region.